Interdisciplinarity: a Current Need to Improve the Teaching-Learning Process - Lizgrace Llano Arana; Miriam Gutiérrez Escobar; Addys Stable Rodríguez; María Cristina Núñez Martínez; Rosa María Masó Rivero; Bárbara Rojas Rivero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
The establishment of interdisciplinary relationships is a present imperative derived from scientific development. Education cannot ignore this development, on the contrary, should integrate it into the teaching process. Educational institutions should promote increased methodological activities, curriculum designs and educational actions using this approach in order to train students in correspondence with the time they live in, which will result in better preparation of professionals. This paper aims to update scholars about the possibilities offered by interdisciplinarity to improve the teaching-learning process. The theoretical and methodological premises of interdisciplinarity are analyzed through a literature review. It also presents different experiences from the implementation of this approach, which have enabled ratifying the need for interdisciplinary relationships in the teaching-learning process, the difficulties encountered when designing a proposal using this approach, and the benefits of its application.